Pengaruh Kualitas Layanan dan Kepercayaan Terhadap Kepuasan Nasabah (Studi Kasus Pada Nasabah BPR BKK Blora) Kantor Cabang Blora - Meliana Nur Azizah, Siti; Maskur, Ali (Journal of Accounting and Finance Management, 2024)
Customer satisfaction has become a critical component in today's industrial environment. The purpose of this study is to investigate how service quality and trust affect credit customers' satisfaction levels, with a focus on the consumers of the BPR BKK Blora Branch Office. This study aims to evaluate the connection between bank credit customers' satisfaction and the caliber of services rendered. Using a quantitative methodology, the study examines primary data gathered from 99 respondents who answered a survey sent via Google Forms. The study's conclusions provide insightful information about bank customer satisfaction and show a strong relationship between customer service standards and PT BPR BKK Blora's dependability.